2011
DOI: 10.1093/carcin/bgr198
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of RANKL/RANK signaling by osteoprotegerin suppresses bone invasion by oral squamous cell carcinoma cells

Abstract: Oral squamous cell carcinomas (OSCCs) are malignant tumors that frequently invade the maxilla and mandibular bone. However, the molecular mechanisms underlying bone invasion by OSCC are unclear. Recent studies showed that receptor activator of nuclear factor κB (RANK) was expressed not only in osteoclast precursors but also in tumor cells. Therefore, we examined whether RANK ligand (RANKL)/RANK signaling regulates bone invasion by OSCC cells in vivo and in vitro. We first injected human OSCC B88 cells into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
0
20
0
2
Order By: Relevance
“…Thus, the suppressive effect of OPG on B88 tumor burden is attributed to increased cell death rather than inhibition of proliferation. However, OPG did not affect apoptosis and proliferation of B88 cells in vitro, suggesting that effects of OPG on apoptosis in B88 cells are restricted to the bone environment (48).…”
Section: The Role Of Rankl/rank Signaling On Bone Invasion By Oral Sccsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, the suppressive effect of OPG on B88 tumor burden is attributed to increased cell death rather than inhibition of proliferation. However, OPG did not affect apoptosis and proliferation of B88 cells in vitro, suggesting that effects of OPG on apoptosis in B88 cells are restricted to the bone environment (48).…”
Section: The Role Of Rankl/rank Signaling On Bone Invasion By Oral Sccsmentioning
confidence: 84%
“…To support these results, RANKL enhanced B88 cell migration in a modified chemotaxis chamber equipped with a gelatin-coated filter. This effect was inhibited by OPG (48).…”
Section: The Role Of Rankl/rank Signaling On Bone Invasion By Oral Sccsmentioning
confidence: 89%
“…RANKL inhibition by using recombinant OPG was also examined in patients with breast cancer or multiple myeloma with osteoclastic bone lesions [93]. Shin et al found that treatment with OPG decreased bone invasion of human OSCC B88 cells, while being injected into the masseter region of nude mice [94]. These examples have reminded researchers of the area of bone invasion.…”
Section: Discussionmentioning
confidence: 99%
“…OPG, a soluble form of TNF receptor family of proteins, is a decoy receptor for the receptor activator of nuclear factor (NF)-kB ligand. 72,73 By binding receptor activator of NF-kB ligand, OPG inhibits NF-kB and therefore prevents inflammation. 74 OPG also promotes osteoclast formation by preventing apoptosis through TNFrelated apoptosis-inducing ligand.…”
Section: Significance Of Sasp Markers At Termmentioning
confidence: 99%